Varicella Zoster Virus infects mucosal associated Invariant T cells - Purohit, Shivam K.; Corbett, Alexandra J.; Slobedman, Barry; Abendroth, Allison (Frontiers in Immunology, 2023)
Mucosal Associated Invariant T (MAIT) cells are innate-like T cells that respond to conserved pathogen-derived vitamin B metabolites presented by the MHC class I related-1 molecule (MR1) antigen presentation pathway. Whilst viruses do not synthesize these metabolites, we have reported that varicella zoster virus (VZV) profoundly suppresses MR1 expression, implicating this virus in manipulation of the MR1:MAIT cell axis. During primary infection, the lymphotropism of VZV is likely to be instrumental in hematogenous dissemination of virus to gain access to cutaneous sites where it clinically manifests as varicella (chickenpox). However, MAIT cells, which are found in the blood and at mucosal and other organ sites, have yet to be examined in the context of VZV infection. The goal of this study was to examine any direct impact of VZV on MAIT cells. Using flow cytometry, we identify primary blood-derived MAIT cells as being permissive to VZV infection. A consequence of VZV infection of MAIT cells was their capacity to transfer infectious virus to other permissive cells, consistent with MAIT cells supporting productive infection. When subgrouping MAIT cells by their co-expression of a variety cell surface markers, there was a higher proportion of VZV infected MAIT cells co-expressing CD4+ and CD4+/CD8+ MAIT cells compared to the more phenotypically dominant CD8+ MAIT cells, whereas infection was not associated with differences in co-expression of CD56 (MAIT cell subset with enhanced responsiveness to innate cytokine stimulation), CD27 (co-stimulatory) or PD-1 (immune checkpoint). Infected MAIT cells retained high expression of CCR2, CCR5, CCR6, CLA and CCR4, indicating a potentially intact capacity for transendothelial migration, extravasation and trafficking to skin sites. Infected MAIT cells also displayed increased expression of CD69 (early activation) and CD71 (proliferation) markers. These data identify MAIT cells as being permissive to VZV infection and identify impacts of such infection on co-expressed functional markers.